2021
DOI: 10.5696/2156-9614-11.30.210607
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale Farmer Pesticide Knowledge and Practice and Impacts on the Environment and Human Health in Ethiopia

Abstract: Background. Inappropriate use and application of pesticides in Ethiopia pose a major threat to the health of farmers and the environment. Objective. The present study aimed to assess the level of knowledge, attitudes, and practices of small-scale vegetable farmers towards the use of pesticides in Ethiopia along the Lake Ziway watershed. Methods. This was a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 45 publications
(74 reference statements)
2
15
0
1
Order By: Relevance
“…A possible explanation for the occurrence of this fungicide that accumulated on the HP-20 passive sampler could be the spray drift during aerial application of pesticides on vegetables, which is a common practice in the study area. The concentration of metalaxyl in HP-20 resin deployed at sampling site 2 (near floriculture enterprise) was significantly lower than the other sampling sites, where intensive vegetable farming activities by small scale farmers (S1 S4 and S5, sampling sites), this was probably that improper use and over the use of pesticides (including metalaxyl) by small scale farmers in the area [4,5,7].…”
Section: The Concentration Of Pesticides In the Passive Samplersmentioning
confidence: 79%
See 4 more Smart Citations
“…A possible explanation for the occurrence of this fungicide that accumulated on the HP-20 passive sampler could be the spray drift during aerial application of pesticides on vegetables, which is a common practice in the study area. The concentration of metalaxyl in HP-20 resin deployed at sampling site 2 (near floriculture enterprise) was significantly lower than the other sampling sites, where intensive vegetable farming activities by small scale farmers (S1 S4 and S5, sampling sites), this was probably that improper use and over the use of pesticides (including metalaxyl) by small scale farmers in the area [4,5,7].…”
Section: The Concentration Of Pesticides In the Passive Samplersmentioning
confidence: 79%
“…A survey study conducted along Lake Ziway showed that intensive use of metalaxyl was reported by small-scale farmers [7], which might be a reason for the presence of metalaxyl in such a high concentration. A possible explanation for the occurrence of this fungicide that accumulated on the HP-20 passive sampler could be the spray drift during aerial application of pesticides on vegetables, which is a common practice in the study area.…”
Section: The Concentration Of Pesticides In the Passive Samplersmentioning
confidence: 99%
See 3 more Smart Citations